PENGEMBANGAN BISNIS INDUSTRI KREATIF BIDANG FESYEN DENGAN PENDEKATAN EKSPOR UNTUK MEMPERKUAT PEREKONOMIAN NASIONAL - Dellia Mila Vernia (UNIVERSITAS INDRAPRASTA PGRI, 2015)
This research aims to determine the development of creative industry fields of fashion, creative industries business role in the economy, barriers encountered, how to develop a strategy, the benefits of the Internet for business development of creative fields of fashion industry, and know the role of government. The method used is a qualitative descriptive study literature. According to writing shows that fashion in Indonesia is still influenced by the culture of Europe and Asia, today, especially from Korea. The creative industry has a role as the fashion field into potential industry and featured contributor to GDP for Indonesia and also as an employer. Barriers facing them in terms of human resources and technology. Strategy for business development among others, to develop human resources and strengthen a strong and competent production with better technology. Benefits include internet creates for the customer base and product and market analysis. The role of government regulations that could make them a conducive business environment and facilitate the creation of a local trend.